RANCANG BANGUN SISTEM INFORMASI KASIR PENJUALAN SOUVENIR PADA TOKO MERAH PUTIH - Ghina Tripasha; Emy LenoraTatuhey (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
The issues of efficiency and accuracy in transaction recording remain major obstacles for small and medium-sized enterprises, particularly in the retail sector such as souvenir shops. Many of them still use manual recording methods, which not only slow down service processes but also increase the risk of errors and make it difficult to compile reports. This study aims to design and implement a web-based cashier information system at Merah Putih Souvenir Shop to support more efficient and accurate business processes. The method used is prototyping, which allows the system to be developed in stages with direct input from users at each stage. The system was developed using PHP Native as the programming language and MySQL as the database management system, and run on a local server using XAMPP. Testing was conducted using the black-box method, which aims to test each function of the system without looking at the internal structure of the code. The test results showed that the system was able to perform its main functions well, such as real-time transaction recording, inventory and stock management, and automatic and accurate sales and stock report generation. With the implementation of this system, transaction processes become faster, with minimal errors, and reports can be accessed more easily. This cashier information system is expected to serve as an efficient, practical, and affordable digital solution for SMEs, thereby enhancing their competitiveness in the digital era